Pelanggaran Etika Iklan Holywings Pada Media Sosial Instagram - Maretha Azzuhriyah; Jamiati KN (Sekolah Tinggi Agama Buddha Nalanda, 2023)
Apart from the positive aspects of using media social, especially Instagram, it is possible that there will also be some negative impacts, such as violating ethics by using the platform to spread hoaxes, slander, insults, blasphemy and other offensive language. For this reason, all advertisers must uphold the Advertising Ethics which have been regulated in a guideline, namely the Indonesian Advertising Ethics (EPI). The Indonesian Advertising Ethics (EPI) serves as a guide for advertising in Indonesia, as well as a guide for addressing this issue. An Instagram post made by Holywings is the subject of qualitative research method content analysis techniques this time. According to the findings of the post content review, there are ethical violations in social media advertising, including violations involving content that offends SARA and illegal content.